The Only Way into Digital Audio Broadcasting - 孙金荣; 李晓芳 (Tongxin xuebao)
A new kind of radio-digital audio broadcasting is presented,application and evolution of digital audio broadcasting as well as in the world.Based on the international,experiences ,some possible ways are proposed on development of digital audio broadcasting for China. The standards of digital audio broadcasting should be determined for China after the software and hardware testing.